Fashion lab as a factor of innovation in fashion authoring design (ModaPalavra e-periódico, 2020)
The post-industrial revolution transformations continue to echo in our society, allowing advances in the area of technology, production, and consumption of products in different segments, especially fashion. In view of this, this article proposes to understand, in an initial and conceptual way, the use of space Fashion lab by fashion designer designers. It is considered that the use of this laboratory can qualify the innovation process during the production of new products. In this work, the basic research was used with a descriptive qualitative approach and the theoretical foundation contemplates the concepts of innovation, fab lab, fashion lab, and authorial design. Finally, the research results indicate that the principles of sharing, experimentation, and prototyping corroborate to the innovation in fashion authoring design in fashion labs.
Keywords: fashion lab; authorial design; innovation